Membrane filtration of collected stormwater for water harvesting - Hey, Tobias ; 0000-0001-5233-836X; Takman, Maria; Lipnizki, Frank ; 0000-0002-3008-0182; Norlander, Helena; Aspegren, Henrik ; 0000-0001-5805-1589; Jephson, Therese (NORDIWA 2023, Göteborg, Sweden, 2023-09-05 - 2023-09-07, 2023)
Stormwater generated during heavy rainfall needs to be managed to prevent flooding and water pollution. In Sweden, drinking water is also used for non-food purposes like irrigation and toilet flushing. To address this, reusing stormwater for non-food purposes through rainwater harvesting can be a solution, which involves collecting and storing rainwater for later use from sources like rooftops, dams or ponds. In the European Union's Horizon 2020 project REWAISE, the use of stormwater collected from the Brunnshög catchment area in Lund was investigated for purposes such as irrigation and toilet flushing. The collected stormwater was used as feed and pumped directly to a membrane pilot plant. The pilot plant consisted of a membrane tank containing submerged flat-sheet silicon carbide (SiC) ceramic membranes with a nominal pore size of 0.2 μm and a total membrane surface area of 4.24 m². During stable operation, grab samples were taken from both the feed and permeate, which were analyzed at an accredited laboratory for SS, CODCr, TOC, Ptot, Ntot, heavy metals, and indicating microorganisms. The results were later compared with the European (EU 2020/741) and the USA (EPA, 2012) requirements for water reuse. Microfiltration was conducted for a total of 19 working days, with an average flux of 25 l/m²·h. The analysis results indicated low concentrations in the permeate of SS (<2.0 mg/l), CODCr (16.3 mg/l), TOC (8.8 mg/l), Ptot (1.5 mg/l), and Ntot (0.9 mg/l), corresponding to rejections of greater than 94% (SS), 65% (CODCr), 44% (TOC), 59% (Ptot), and 40% (Ntot). The average concentrations of heavy metals in the permeate and corresponding rejections were as follows: Zn (8.01 μg/l, 84%), Pb (<0.5 μg/l, >82%), Ni (5.77 μg/l, 68%), Cr (<0.5 μg/l, >66%), Cu (6.04 μg/l, 45%), and As (1.75 μg/l, 43%). Cd and Hg were below <0.1 μg/l in both the feed and the permeate. The concentration of indicating microorganisms in the permeate was as follows: Clostridium perfringens (1 cfu/100 ml), coliform bacteria (259 cfu/100 ml), E. coli (16 mpn/100 ml), and Enterococci (151 mpn/100 ml). The study demonstrated the feasibility of using stormwater as a water source by meeting the European minimum requirements for water quality for "reclaimed water quality class B." Additionally, the study also met the US EPA requirements for heavy metal. Although the average concentrations of microorganisms were not achieved due to contamination in the permeate pipe, 9 out of 13 samples showed E. coli concentrations of ≤ 10 cfu/100 ml, indicating that the permeate could also be used for irrigation of crops. The results suggest that the produced permeate could be used not only for toilet flushing, but also for irrigation purposes, potentially reducing the need for drinking water. Acknowledgment This research is partially funded by the REWAISE project, titled ‘Resilient Water Innovation for Smart Economy,’ which is part of the European Horizon 2020 program (Project No. 869496). References Regulation (EU) 2020/741 of the European parliament and of the council of 25 May 2020 on minimum requirements for water reuse. Guidelines for Water Reuse 2012, AR-1530, EPA/600/R-12/618, United States Environmental Protection Agency.
Keywords: Membrane processess; Rainwater harvesting; Drinking water